REPRODUCTIVE MADANIYATNI SHAKLLANTIRISHNING HISTORICAL AND HISTORICAL DEVELOPMENT - Jumanova Fatima Urolovna; Yaxshimbekova Sayyora Kamalovna (American Journals Publishing, 2023)
Today's pressing task of government policy and its legal significance in educating future physical education teachers about their reproductive culture. This article is devoted to the historical and evolutional development of the formation of reproductive culture.
Keywords: physical education, reproductive culture, government policy, intellectual heritage, human values, culture, economics, science and technology, technology.